Effect of damping force on CIT and QIT ion traps supplied with periodic impulse voltage form. - Sadat Kiai, S. M.; Seddighi Chaharborj, Sarkosh; Abu Bakar, Mohd Rizam; Ismail, Fudziah (Royal Society of Chemistry, 2011)
The behavior of confined ions under a damping force based on laser or collisional cooling is of particular importance in different disciplines especially in high resolution mass spectrometry. The significance of the effect of the damping force on confined ions in a cylindrical ion trap has not been yet investigated, so, in this article a cylindrical ion trap excited with a periodic impulse voltage of the form f(t)¼V0cosUt/(1-kcos2Ut) with 0#k < 1 is studied and compared to the quadrupole ion trap with and without the effect of damping force. Numerical computations allowed the determination of the twelve stability diagrams using fifth order Runge–Kutta derivative approximations. The physical properties of the confined ions in the r and z axis are illustrated and the effect of damping force on the fractional mass resolutions m/Dmof the confined ions in two first and second stability regions of both ion traps was analyzed.